Pengaruh Perkecambahan terhadap Sifat Fungsional Jewawut: Tinjauan Komprehensif - Indrastuti, Indrastuti; Wakiah, Nurul; Islamiyah, Syahmidarni Al (Program Studi Teknologi Hasil Pertanian Fakultas Sains dan Teknologi Hasil Pertanian Universitas Muhammadiyah Sidenreng Rappang, 2025)
ABSTRACT Pearl millet, a resilient and nutritious cereal crop, plays a crucial role in ensuring food security in arid and semi-arid regions worldwide. Despite its importance, there is limited research on the physicochemical changes and functional properties of pearl millet during germination. This study aims to systematically review and synthesize existing literature to bridge this knowledge gap and provide insights into the potential of germinated pearl millet in functional food development. We hypothesize that germination significantly enhances the functional properties of pearl millet by altering its physicochemical characteristics. Previous studies have documented various biochemical and structural transformations in pearl millet during germination, including changes in enzyme activity, nutrient composition, and bioactive compounds. However, a comprehensive analysis of how these changes specifically influence the functional properties of pearl millet is lacking. By investigating these transformations, we can optimize the use of pearl millet in developing functional foods that cater to health-conscious consumers and address specific dietary needs or health concerns. This research will contribute to a better understanding of the nutritional and functional potential of germinated pearl millet, ultimately leading to innovative food products and improved food security in regions where pearl millet is a staple crop.